2009
DOI: 10.1099/jmm.0.007732-0
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and detection of Shiga toxin-producing Escherichia coli in clinical stool samples using conventional and molecular methods

Abstract: The isolation of Shiga toxin-producing Escherichia coli (STEC) other than serogroup O157 from clinical stool samples is problematic due to the lack of differential phenotypic characteristics from non-pathogenic E. coli. The development of molecular reagents capable of identifying both toxin and serogroup-specific genetic determinants holds promise for a more comprehensive characterization of stool samples and isolation of STEC strains. In this study, 876 stool samples from paediatric patients with gastroenteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
25
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 35 publications
3
25
0
Order By: Relevance
“…However, higher isolation rate (7.5%) was reported in a different study in South Africa [43]. The isolation of non-O157 strains from human stools (2.7%) in the present study was comparable to 2.5% reported in Canada [44] and USA, where 4.2% of stool sample were positive [45]. …”
supporting
confidence: 72%
“…However, higher isolation rate (7.5%) was reported in a different study in South Africa [43]. The isolation of non-O157 strains from human stools (2.7%) in the present study was comparable to 2.5% reported in Canada [44] and USA, where 4.2% of stool sample were positive [45]. …”
supporting
confidence: 72%
“…Other studies have reported higher success rates for STEC isolation by culture if serotypes other than O157 are also searched for (14,15,40). But in the routine laboratory, STECs other than O157 cannot be detected by means other than PCR aimed at the stx 1 and/or stx 2 genes.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, methods which quickly identify the negative specimens would facilitate routine screening. Antigen detection is a fast and effective alternative for several enteric pathogens (11,15,23,27,46). However, this method has a limited sensitivity, requires one test per pathogen, and is not available for all relevant pathogens.…”
mentioning
confidence: 99%
“…All these stool samples had been previously identified 27 to contain positive cultures of the following: O157:H7; O26:H11; O121:H19; O26:NM; O5:NM; O111: NM; O145:NM; O103:H2; O177:NM; O1:H7; O8:H19; O2: H4; and O25:H1.…”
Section: Evaluation Of Pcr Platformsmentioning
confidence: 99%
“…A total of 36 stool samples previously identified 27 to contain the following 41 STEC strains (co-infection was found in five samples) were included in the study: O157:H7 (n ϭ 18); O26:H11 (n ϭ 10); O121:H19 (n ϭ 3); O26:NM (n ϭ 1); O5:NM (n ϭ 1); O111:NM (n ϭ 1); O145:NM (n ϭ 1); O103:H2 (n ϭ 1); O177:NM (n ϭ 1); O1:H7 (n ϭ 1); O8:H19 (n ϭ 1); O2:H4 (n ϭ 1); and O25:H1 (n ϭ 1).…”
Section: Enrichment Of Stec In Stool Samples and Dna Extractionmentioning
confidence: 99%